2005
DOI: 10.1111/j.1572-0241.2005.41384.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Eradicating Helicobacter Pylori on the Development of Gastric Cancer in Patients with Peptic Ulcer Disease

Abstract: H. pylori eradication may reduce their risk of developing gastric cancer in patients with gastric ulcer. Large-scale studies in additional populations of this important international public-health issue are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
190
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(204 citation statements)
references
References 19 publications
7
190
0
5
Order By: Relevance
“…However, many of these included cases whose cancer lesions developed relatively soon after eradication, namely within 2 years after the treatment (Take et al 2005;Kamada et al 2005;Takenaka et al 2007;Fukase et al 2008;Ogura et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, many of these included cases whose cancer lesions developed relatively soon after eradication, namely within 2 years after the treatment (Take et al 2005;Kamada et al 2005;Takenaka et al 2007;Fukase et al 2008;Ogura et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…There have been several reports that showed the incidence and characteristic features of gastric cancer after H. pylori eradication (Take et al 2005;Kamada et al 2005;Takenaka et al 2007;Fukase et al 2008;Ogura et al 2008;Yanaoka et al 2009;de Vries et al 2009). However, many of these included cases whose cancer lesions developed relatively soon after eradication, namely within 2 years after the treatment (Take et al 2005;Kamada et al 2005;Takenaka et al 2007;Fukase et al 2008;Ogura et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Graham [4] and Uemura et al [6] reported that approximately 20% of H. pylori-infected individuals develop clinically significant diseases, and the frequency of duodenal ulcers in individuals with H. pylori infection is thought to be approximately 16% [4]. Although Fischer et al [7] found 48 cases of concomitant gastric cancer while reviewing 45000 patients with duodenal ulcer (0.1%), Miwa et al [8] stated that six patients with gastric cancer among their 356 patients (1.7%) also showed duodenal ulcers, and Take et al [9] and Kamada et al [10] reported that gastric cancer did not develop in patients with duodenal ulcer. Uemura et al [6] conducted a 5-year follow-up of many Japanese subjects with H. pylori infections and found that all those with duodenal ulcers were also infected with H. pylori; however, none of the patients with duodenal ulcer developed gastric cancer, although 3.4% of the patients with gastric ulcer did, and gastric cancer subsequently appeared in 5% of the patients with H. pylori infections.…”
Section: Frequencies Of Duodenal Ulcer and Gastric Cancermentioning
confidence: 99%
“…Intervention studies conducted in Latin America and Asia and meta-analysis have shown that H pylori eradication is an effective step in preventing gastric cancer, particularly if treatment is performed on patients prior to development of precancerous conditions (atrophic gastritis and intestinal metaplasia) (65,139,193,206,210) . Studies using animal models have also confirmed that gastric cancer development can be prevented by early eradication of the microorganism (14,151) .…”
Section: Statement 17mentioning
confidence: 99%